The investment in the audiovisual sector: Role of the audiovisual control authority - Nekkache, Hamza (Journal of Human Sciences, 2020)
The audiovisual activity is one of the most important areas that individuals seek to invest in in order to exercise freedom from recognized public freedoms and it is the freedom of audiovisual communication, although the legislator recognized the freedom to invest in this field, and he created a regulatory authority in it to announce the opening of the private initiative after it was monopolized On the part of the state, however, there are some restrictions imposed by the legislator to enter this sector, including obtaining an authorization that gave him authority to grant it to the executive authority, unlike other sectors that give the authority to allow entry to the market to the regulatory authority, and the legislator has only granted the regulatory authority the authority a Prepare for the granting of the authorization and study the files and to conclude agreements with the beneficiary of the authorization, but in return has given broad powers of control and punishment for violators of the provisions of the legal and regulatory organization for the sector.